Challenging catheter management in a rare case of myelomeningocele with situs inversus totalis: a case report - Ismail, Hazwani; Wan Zukiman, Wan Zul Haikal Hafiz (Longe Medikal, 2024)
Patients with situs inversus totalis and renal failure encounter unique challenges, including heightened risks of vascular stenosis and thrombosis during dialysis due to altered blood flow patterns. A 19-year-old female with myelomeningocele and situs inversus totalis faces ESKD due to bladder dysfunction. Since her vascular access was unsuitable, she started hemodialysis with the right catheter (23cm cuff to tip). Unfortunately, she developed an MSSA central line-associated bloodstream infection, causing septic shock. CT and echocardiogram showed 9-mm tricuspid vegetation near the cavoatrial junction. She was discharged with a 19-cm permanent catheter after six weeks of intravenous cloxacillin. Patients with ESKD are at high risk for various vascular complications that can have significant repercussions if left untreated, and individuals with situs inversus face even more challenges. Inserting a catheter in a patient with dextrocardia can be difficult and complex, potentially requiring specific manoeuvres. They also possess unique vascular anatomy that cannot be managed in the same way as a typical ESKD patient. Therefore, it is critical to employ sterile methods, select an appropriate catheter size and type, and utilise imaging tools like ultrasound or venography to guide insertion and minimise the risk of complications. Situs inversus totalis complicated renal failure management.